2020
DOI: 10.1136/gutjnl-2020-321173
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria-derived long chain fatty acid exhibits anti-inflammatory properties in colitis

Abstract: ObjectiveData from clinical research suggest that certain probiotic bacterial strains have the potential to modulate colonic inflammation. Nonetheless, these data differ between studies due to the probiotic bacterial strains used and the poor knowledge of their mechanisms of action.DesignBy mass-spectrometry, we identified and quantified free long chain fatty acids (LCFAs) in probiotics and assessed the effect of one of them in mouse colitis.ResultsAmong all the LCFAs quantified by mass spectrometry in Escheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
108
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(116 citation statements)
references
References 52 publications
6
108
2
Order By: Relevance
“…33,51,52 Partly in line with our findings, previous studies have shown that H. biformis displays anti-inflammatory and antitumourigenic effects through both SCFAs and LCFAs production, 30,31 which are also PYY and GLP-1 secretagogues. 53 H. biformis could contribute to increasing the levels of oleic and α linolenic acid through its own capacity to produce C18 FAs, 31 amplifying some of the HFHSD-associated effects. Furthermore, H. biformis-induced changes in gut microbiota composition might also account for changes in intraluminal LCFAs metabolism.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…33,51,52 Partly in line with our findings, previous studies have shown that H. biformis displays anti-inflammatory and antitumourigenic effects through both SCFAs and LCFAs production, 30,31 which are also PYY and GLP-1 secretagogues. 53 H. biformis could contribute to increasing the levels of oleic and α linolenic acid through its own capacity to produce C18 FAs, 31 amplifying some of the HFHSD-associated effects. Furthermore, H. biformis-induced changes in gut microbiota composition might also account for changes in intraluminal LCFAs metabolism.…”
Section: Discussionsupporting
confidence: 91%
“…Partly in line with our findings, previous studies have shown that H . biformis displays anti‐inflammatory and antitumourigenic effects through both SCFAs and LCFAs production, 30,31 which are also PYY and GLP‐1 secretagogues 53 …”
Section: Discussionmentioning
confidence: 99%
“…The production of it by bacteria could be one of the mechanisms implicated in the anti-in ammatory properties of probiotics. In addition, C18-3OH correlated with an increase in the abundance in Holdemanella (49). In a previous animal study, higher loading of Holdemanella and Desulfovermiculus were found in Obsessive-compulsive patients (50).…”
Section: Discussionmentioning
confidence: 63%
“…Peak detection, integration, and quantitative analysis were performed with MassHunter Quantitative analysis software (Agilent Technologies, Santa Clara, CA, USA). For each standard, calibration curves were built using 10 solutions at concentrations ranging from 0.95 to 500 ng mL −1 [ 69 , 70 ].…”
Section: Methodsmentioning
confidence: 99%